Three-leaf stone masonry repair and strengthening - Silva, Rui André Martins (2008)
This paper summarizes the results of an extensive test campaign over three-leaf stone masonry walls, aiming at studying the behavior of these kind of walls under compressive loading and the effects introduced by the most common strengthening techniques used for structural rehabilitation of heritage buildings. A total of ten three-leaf stone (granite) masonry walls were tested, plain or strengthened resorting to transversal tying with GFRP rods, injection of a lime based grout and both techniques applied simultaneously. In addition, it is also presented the characterization of the materials and of the three-leaf walls components (external and inner leaves). The results show that the strengthening techniques used in this work were effective in different ways.